Reduction of visual acuity decreases capacity to evaluate radiographic image quality. (October 2020) - Sá dos Reis, C.; Soares, F.; Bartoli, G.; Dastan, K.; Dhlamini, Z.S.; Hussain, A.; Kroode, D.; McEntee, M.F.; Mekis, N.; Thompson, J.D.
Abstract: Introduction: To determine the impact of reduced visual acuity on the evaluation of a test object and appendicular radiographs. Methods: Visual acuity was reduced by two different magnitudes using simulation glasses and compared to normal vision (no glasses). During phase one phantom images were produced for the purpose of counting objects by 13 observers and on phase 2 image appraisal of anatomical structures was performed on anonymized radiographic images by 7 observers. The monitors were calibrated (SMPTE RP133 test pattern) and the room lighting was maintained at 7 ± 1 lux. Image display and data on grading were managed using ViewDEX (v.2.0) and the area under the visual grading characteristic (AUCVGC ) was calculated using VGC Analyzer (v1.0.2). Inferential statistics were calculated using SPSS. Results: For the evaluation of appendicular radiographs the total interpretation time was longer when visual acuity was reduced with 2 pairs of simulation glasses (15.4 versus 8.9 min). Visual grading analysis showed that observers can lose the ability to detect anatomical and contrast differences when they have a simulated visual acuity reduction, being more challenging to differentiate low contrast details. No simulation glasses, compared to 1 pair gives an AUCVGC of 0.302 (0.280, 0.333), that decreases to 0.197 (0.175, 0.223) when using 2 pairs of glasses. Conclusions: Reduced visual acuity has a significant negative impact on the evaluation of test objects and clinical images. Further work is required to test the impact of reduced visual acuity on visual search, technical evaluation of a wider range of images as well as pathology detection/characterization performance. Implications for practice: It seems that visual performance needs to be considered to reduce the risks associated with incomplete or incorrect diagnosis. If employers or professional bodies were to introduce regular eye tests into health screening it may reduce the risk of misinterpretation as a result of poor vision.